1988
DOI: 10.1063/1.340062
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling microscopy, lithography, and surface diffusion on an easily prepared, atomically flat gold surface

Abstract: We show that a gold surface with atomically flat terraces as large as (150 nm)2 can be easily prepared in air by melting a gold wire with an oxyacetylene torch. Features with characteristic dimensions as low as 10 nm can be written and observed on these terraces with a scanning tunneling microscope. The features are appreciably distorted by diffusion within an hour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(47 citation statements)
references
References 24 publications
3
44
0
Order By: Relevance
“…Flat gold surfaces were obtained by first melting a small piece of gold; during resolidification small and flat facets are formed. 4 To deposit the clusters onto the substrates, they were first suspended in a mixture of 90% water in 10% pyridin. A drop of this suspension was spread on the substrate and subsequently removed, either by rapidly spinning the substrate or by blowing with pure nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Flat gold surfaces were obtained by first melting a small piece of gold; during resolidification small and flat facets are formed. 4 To deposit the clusters onto the substrates, they were first suspended in a mixture of 90% water in 10% pyridin. A drop of this suspension was spread on the substrate and subsequently removed, either by rapidly spinning the substrate or by blowing with pure nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…This process results in the formation of well-defined Au (111) facets, as reported previously. [30] The gold wire was then sealed into a glass capillary leaving only the gold bead exposed. The gold beads were electrochemically cleaned by electrolysis in 0.1  HClO 4 and the red crust that formed on the surfaces was removed by dipping them into 0.1  HCl.…”
Section: Contact-angle Measurementsmentioning
confidence: 99%
“…Therefore they offer an ideal substrate for STM studies in air and in many electrolytes. Studies such as DNA deposition (Lindsay 81 Barris, 1988), lithography (Schneir et al, 1988a), chemisorption (George et al, 1988) and electrodeposition (Schneir et al, 1988b;Nagahara et al, 1988) have been reported recently. Observation of atomic corrugation on gold surfaces (thought to be impossible due to the intrinsic smoothness of electronic wave functions at the surface) has also been reported recently (Hallmark et al, 1987).…”
Section: Introductionmentioning
confidence: 96%